A mathematical model of respiration in halobacterium salinarum - Talaue, Cherryl O. (Institute of Mathematics, College of Science, University of the Philippines Diliman, 2009)
We present a mathematical model for the respiration in Halobacterium salinarum which agrees with experimental data on oxygen consumption. The model is developed using some basic principles from Biochemical Systems Theory. The biological systems we model consists of the electron transport chain which enhances the proton motive force, the ATP synthase which is driven by the proton motive force, the potassium uniport and sodium-proton antiporter.